Oxygen‐Independent Sulfate Radical for Stimuli‐Responsive Tumor Nanotherapy - Ding, Dandan; Mei, Zihan; Huang, Hui; Feng, Wei; Chen, Liang; Chen, Yu; Zhou, Jianqiao (Advanced science, 2022)
Variant modalities are quested and merged into the tumor nanotherapy by leveraging the excitation from external or intratumoral incentives. However, the ubiquitous hypoxia and the insufficient content of hydrogen peroxide (H2O2) in tumor microenvironments inevitably hinder the effective production of reactive oxygen species (ROS). To radically extricate from the shackles, peroxymonosulfate (PMS: HSO5−)‐loaded hollow mesoporous copper sulfide (CuS) nanoparticles (NPs) are prepared as the distinct ROS donors for sulfate radical (•SO4−)‐mediated and stimuli‐responsive tumor nanotherapy in an oxygen‐independent manner. In this therapeutic modality, the second near‐infrared laser irradiation, together with the released copper ions as well as the heat produced by CuS after illumination, work together to activate PMS thus triply ensuring the copious production of •SO4−. Different from conventional ROS, the emergence of •SO4−, possessing a longer half‐life and more rapid reaction, is independent of the oxygen (O2) and H2O2 content within the tumor. In addition, this engineered nanosystem also exerts the function of photoacoustic imaging and skin restoration on the corresponding animal models. This study reveals the enormous potential of sulfate radical in oncotherapy and broadens pave for exploring the application of multifunctional and stimuli‐responsive nanosystems in biomedicine. The CuS@PMS nanosystems with multiple theranostic functions are maneuverable in stimuli‐responsive sulfate radical‐mediated nanotherapy against melanoma in an oxygen‐independent manner, competent in photoacoustic imaging and precipitating skin regeneration. The high‐performance sulfate radical tumor therapy is implemented via exploiting the outstanding oxidation property of sulfate radical and inducing synergistic activation by photothermal effect and copper ions.